2010
DOI: 10.1155/2010/375245
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Dual-Output Programmable Blocks to Balance Secure Dual-Rail Logics

Abstract: FPGA design of side-channel analysis countermeasures using unmasked dual-rail with precharge logic appears to be a great challenge. Indeed, the robustness of such a solution relies on careful differential placement and routing whereas both FPGA layout and FPGA EDA tools are not developed for such purposes. However, assessing the security level which can be achieved with them is an important issue, as it is directly related to the suitability to use commercial FPGA instead of proprietary custom FPGA for this ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A previous work showed that having the pair of wires pass through the same LUT (by exploiting their dual outputs) can significantly reduce the unbalance [23]. Indeed, the "graph" for both wires is the same.…”
Section: B Timing Faults On Pc-ii With T =mentioning
confidence: 99%
“…A previous work showed that having the pair of wires pass through the same LUT (by exploiting their dual outputs) can significantly reduce the unbalance [23]. Indeed, the "graph" for both wires is the same.…”
Section: B Timing Faults On Pc-ii With T =mentioning
confidence: 99%
“…Similar to the iWDDL approach there is another called divided backend WDDL (DBWDDL) [40] that utilises XOR gates as inverters instead of registers. To ensure balanced routing, one may use dual-output programmable blocks within some FPGA as discussed in [41]. The results of an ASIC implementation of AES algorithm protected with balanced WDDL can be found in [32].…”
Section: Wave Dynamic Differential Logic (Wddl)mentioning
confidence: 99%
“…Each of these is a fundamental operation with easily understood formal properties, yet they mapped cleanly and efficiently to a wide variety of reconfigurable devices. In the same year, Laurent Sauvage et al [13] experimentally gave evidence that differential placement and routing of an FPGA implementation can be done with a granularity fine enough to improve the security gain. However, so far, this gain turned out to be lower for FPGAs than for ASICs.…”
Section: Related Workmentioning
confidence: 99%